Development of modern methodological approaches to assessing the economic security of enterprises - Kuznetsov, Ivan (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to the formation of new scientific methods necessary for developing modern methodological approaches to assessing the economic security of enterprises. This need is especially important given the increasing economic challenges faced by Ukrainian businesses. The scientific and practical necessity of improving the efficiency and effectiveness of economic security management at Ukrainian enterprises has been revealed. The study has also highlighted the key importance of assessing the economic security of enterprises for increasing the resilience of Ukrainian businesses and stimulating the transition to a sustainable development model for the country's economic entities. The aim of the article is to identify ways to develop modern methodological approaches to assessing enterprise economic security. Methodology: A set of general and specific methods has been applied at both empirical and theoretical levels. These include the method of literary analysis to study scientific issues in the field of assessing the economic security of enterprises; methods of induction and deduction to determine the key components of the process of ensuring economic security at Ukrainian enterprises; the benchmarking method for providing critical characteristics to the existing methodical approaches to assessing the economic security of enterprises; methods of analysis and synthesis to form a set of requirements for modern methodical approaches to assessing the economic security of enterprises; methods of systematization, grouping and logical generalization for systematization of information, formation of conclusions and scientific proposals of the article. Results: ways for developing modern methodological approaches to assessing the economic security of Ukrainian enterprises have been identified. Also, the research has determined the key elements involved in creating contemporary methodological approaches for assessing the economic security of enterprises. JEL Classification: D21, L21, M13, М21.